EVALUATION OF ANTI CANCER POTENTIAL OF METHANOL EXTRACT OF CURCUMA ZEDOARIA. - PAL, PROSANTO; PRASAD, ARTI KUMARI; CHAKRABORTY, MAINAK; HALDAR, SAGNIK; MAJUMDER, POULAMI; KANTI HALDAR, PALLAB (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Evaluation of anti cancer activity of methanol extracts of Curcuma zedoaria against Ehrlich’s ascities carcinoma (EAC) cell line in Swiss albino mice. Method: In vitro cytotoxicity assay has been evaluated by using the trypan blue and MTT assay method. In vivo anti cancer activity was performed by using EAC cells induced mice groups (n=12), at the doses of 100 and 200 mg/kg b.w. respectively, half of the mice were sacrificed and the rest were kept alive for life span parameter. The anti cancer potential of MECZ was assessed by evaluating tumor volume, viable and nonviable tumor cell count, tumor weight, hematological parameters and biochemical estimations. Furthermore, antioxidant parameters were assayed by estimating liver tissue enzymes. Result: Dose dependent cytotoxicity was observed in (* p < 0.05) Trypan blue and MTT assay method. In vivo anti cancer parameters like tumor volume, tumor weight, and viable cell count were decreased compared to the EAC control group. MECZ treated EAC cellâ€“bearing mice had an increased life span to that of EAC control group. Hematological and serum biochemical profiles were restored to normal levels in MECZ-treated mice compared to the EAC control group. Among the tissue parameters lipid peroxidation, reduced glutathione,superoxide dismutase, and catalase toward normal levels compared to the EAC control group. In short, Conclusion: MECZ exhibited remarkable antitumor activity in Swiss albino mice, which is attributed to its augmentation of endogenous antioxidant activities and cytotoxic nature. Keywords: Curcuma zedoaria, Zingiberaceae, EAC cell line, antitumor activity, 5-Flurouracil